2019
DOI: 10.1111/dth.13030
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid in a patient treated with nivolumab

Abstract: Lauwers, & Masia, 2017). The prolonged average life of PD-1 inhibitors (Fessas, Lee, Ikemizu, & Janowitz, 2017) and the long-lasting tumor responses due to the persistence of immune activation (Robert et al., 2018; Schadendorf et al., 2017) may explain these delayed cutaneous adverse events. The pathogenesis of bullous pemphigoid (BP) induced by immunotherapy has not been clarified yet (Zhao, Hwang, Consuegra, Chou, & Fernandez-Penas, 2018). Diagnosis and management are similar to BP not associated with immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Reference lists of the 139 eligible articles were also screened for additional articles, and 77 articles met the eligibility criteria after screening. Among these, 70 articles reporting clinical data from 127 individual patients were reviewed to include in the analytic component of the systematic review. The 7 other articles provided predominantly summarized data, with limited and inconsistent data from individual patients.…”
Section: Resultsmentioning
confidence: 99%
“…Reference lists of the 139 eligible articles were also screened for additional articles, and 77 articles met the eligibility criteria after screening. Among these, 70 articles reporting clinical data from 127 individual patients were reviewed to include in the analytic component of the systematic review. The 7 other articles provided predominantly summarized data, with limited and inconsistent data from individual patients.…”
Section: Resultsmentioning
confidence: 99%
“…Our case overlapped with the presentation of bullous pemphigoid and initiation of nivolumab occurring eleven months after initiation. One proposed reason why bullous pemphigoid occurs months after initiation of nivolumab is the long average life of PD-1 inhibitors and the persistence of immune response with these agents [ 9 ]. The reported average half-life of nivolumab is approximately twenty-seven days with a steady-state of twelve weeks [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the MEDLINE search of PubMed, it is worth noting that most of the case reports and case series detailed bullous pemphigoid occurring while receiving nivolumab [ 3 , 5 , 6 ]. Three separate articles detail the development of bullous pemphigoid after discontinuation of nivolumab [ 3 , 9 , 11 ]. Our case fits into the latter category of developing bullous pemphigoid following discontinuation of nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence showed that the median number of weeks of immunotherapy prior to onset of BP was 17 (range of 3 to 91) [7] . However, delayed cases have been reported, even several months after discontinuation of immunotherapy [8,9] .…”
Section: Discussionmentioning
confidence: 99%